2001
DOI: 10.1007/s002460010178
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life 20 and 30 Years After Surgery in Patients Operated on for Tetralogy of Fallot and for Atrial Septal Defect

Abstract: Follow-up studies on patients operated on for congenital heart defects have shown good anatomical results and long-term survival. To date, there have been few studies on such patients with regard to long-term psychosocial outcome and quality of life. In this study, two cohorts of patients operated on before the age of 15 years, one for tetralogy of Fallot (TOF) and the other for atrial septal defect (ASD), were investigated 20 and 30 years after operation regarding quality of life. The combined cohort had a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
46
4
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 16 publications
10
46
4
1
Order By: Relevance
“…The interviews gave no indication of poor psychosocial adaptation or quality of life; instead the interviewees' quality of life was good and was not affected by the heart disease. This is consistent with findings by Ternestedt et al [7] that patients with a mild heart defect, atrial septal defect, and patients with a more severe defect tetratology of Fallot, both report high quality of life 20-30 years after surgery. Surprisingly, the tetratology of Fallotgroup rated their quality of life higher than did the atrial septal defect group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The interviews gave no indication of poor psychosocial adaptation or quality of life; instead the interviewees' quality of life was good and was not affected by the heart disease. This is consistent with findings by Ternestedt et al [7] that patients with a mild heart defect, atrial septal defect, and patients with a more severe defect tetratology of Fallot, both report high quality of life 20-30 years after surgery. Surprisingly, the tetratology of Fallotgroup rated their quality of life higher than did the atrial septal defect group.…”
Section: Discussionsupporting
confidence: 93%
“…Such problems are compounded by distressing signs and symp-0167-5273/$ -see front matter D 2005 Elsevier Ireland Ltd. All rights reserved. doi:10.1016/j.ijcard.2005.08.006 toms of the cardiac disease: chest pain, palpitations, arrhythmias, blue fingertips and lips, fatigue, chest deformation and scars [6,7]. On the other hand, objective physical data, such as cyanosis, cardiac failure or arrhythmia are not significantly correlated to the patients' health-related quality of life or subjective health status [8].…”
Section: Introductionmentioning
confidence: 97%
“…Surprisingly, comparison of patient subgroups showed that neither the severity of illness nor the presence of cyanosis had an impact on QOL. Ternested et al [20] reported similar findings.…”
Section: Discussionmentioning
confidence: 61%
“…To date, all published studies examining quality of life issues in adults with congenital heart disease have used the need approach. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In these studies, quality of life was measured from a functional or socioeconomic, rather than an individual, perspective. The former approach typically uses standardized questionnaires or classification systems.…”
Section: Discussionmentioning
confidence: 99%